N6-methyladenosine mRNA methylation is important for the light response in soybean - Zhang, Liya; Zhang, Yanyan; Liu, Jun; Li, Hongyu; Liu, Bin; Zhao, Tao (Frontiers in Plant Science, 2023)
N6-methyladenosine (m6A) modification of messenger RNA (mRNA) is the most prevalent and abundant modification in eukaryotic mRNA and posttranscriptionally modulates the transcriptome at almost all stages of mRNA metabolism. In plants, m6A is crucial for embryonic-phase growth, flowering time control, microspore generation and fruit maturation. However, the role of m6A in plant responses to light, the most important environmental stimulus, remains unexplored. Here, we profile the m6A transcriptome of Williams 82, a soybean cultivar, and reveal that m6A is highly conserved and plays an important role in the response to light stimuli in soybean. Similar to the case in Arabidopsis, m6A in soybean is enriched not only around the stop codon and within the 3’UTR but also around the start codon. Moreover, genes with methylation occurring in the 3'UTR have higher expression levels and are more prone to alternative splicing. The core genes in the light signaling pathway, GmSPA1, GmPRR5 and GmBIC6, undergo changes in methylation modification and transcription levels in response to light. KEGG pathway analysis revealed that differentially expressed genes with differential m6A peaks were involved in the “photosynthesis” and “circadian rhythm” pathways. Our results highlight the important role played by epitranscriptomic mRNA methylation in the light response in soybean and provide a solid basis for determining the functional role of light on RNA m6A modification in this plant.